Bioactive peptides: Synthesis, applications, and associated challenges - Alzaydi, Abrar; Barbhuiya, Rahul Islam; Routray, Winny; Elsayed, Abdallah; Singh, Ashutosh (Food bioengineering, 2023)
Bioactive peptides (BPs) are chains of amino acids linked together by peptide bonds and arranged in a specific way. These peptides are important to human health and can be used in preserving food. The interest in BPs and its benefits has led to increased production from different food sources and advanced technology to extract them in their pure form. This review explores the subject of BP sources, their synthesis, and their application in various fields, including food and pharmaceuticals. Each source has its unique characteristics, types of peptides, and sequences. The sequence of each peptide extracted from different sources differs in their arrangement and effect on disease treatment. Despite the interest in BPs, challenges remain in their fractionation and purification. Further research is needed to fully exploit the potential of this diverse group of compounds for successful future applications.